Nephropathy 1st inhibits renal fibrosis by activating the PPARγ signaling pathway - Mu, Linjie; Zhu, Liting; Feng, Yuan; Chen, Nianzhao; Wang, Feng; He, Lijuan; Cheng, Jinguo (Frontiers in Pharmacology, 2022)
Renal fibrosis is a manifestations of kidney injury. Nephropathy 1st is a traditional Chinese herbal medicine which was used as a therapy for kidney disease, but the underlying mechanisms remain elusive. The aim of this study was to investigate the role and underlying mechanisms of Nephropathy 1st on the progression of kidney disease. In the present study, unilateral ureteral obstruction was performed to establish the renal fibrosis rat model. By Hematoxylin–Eosin (HE) staining and immunohistochemical staining (IHC) analysis, the severity of renal fibrosis was evaluated in vivo. Serum creatinine (CREA) and urea nitrogen (BUN) were measured by ELISA. The expression levels of Col-I, FN, PPARγ and Klotho were measured by Western blot in rat NRK-49F cells and in fibrotic rats. GW9662 was used to inhibit PPARγ signaling. Metabonomic analysis showed metabolic differences among groups. Nephropathy 1st administration alleviated the progression of rat renal fibrosis, and reduced serum creatinine (Scr) and BUN levels. Mechanistically, Nephropathy 1st promoted the expression of PPARγ and thus activated PPARγ signaling. thereby reduced the pro-fibrotic phenotypes of fibroblasts. The therapeutic effect of Nephropathy 1st was abrogated by a PPARγ inhibitor GW9662. Moreover, Nephropathy 1st normalized the dysregulated lipid metabolism in renal fibrosis rats. In conclusion, Nephropathy 1st alleviates renal fibrosis development in a PPARγ- dependent manner.